Drivers for green building: A review of empirical studies. (February 2017) - Darko, Amos; Zhang, Chenzhuo; Chan, Albert P.C.
Abstract: This paper presents a comprehensive literature review of what drives the adoption of green buliding (GB) practices among construction stakeholders. The review is based on literature that have been published in peer-reviewed journals. Through a systematic review of the literature, authors are able to identify generic drivers for stakeholders to pursue GB. A total of 64 drivers were identified from reviewing 42 selected empirical studies. The paper presents a classification framework for the GB drivers. The framework comprises five main categories of GB drivers: external drivers, corporate-level drivers, property-level drivers, project-level drivers, and individual-level drivers. The US, Australia, UK, India, and China have been the leading countries in GB drivers research. Survey and descriptive statistics have seen widespread use in examining GB drivers. While there is scope for more detailed investigations on GB drivers in developed countries, much more scope exists in developing countries. This paper would enhance policy makers' and advocates' understanding of drivers for GB and help to further promote the GB concept. As a result of the checklist and framework on GB drivers, this paper also lays a solid foundation for researchers to further probe into the topic and add to the knowledge base. Highlights: Academic literature on green building drivers has been reviewed. 64 drivers for implementing green building were identified. A classification framework for green building drivers has been presented. The leading countries in green building drivers research have been identified.